(untitled) (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
Three maps that provide multiple understandings and information that transcend time and space, bringing together lives, traditions and memories that lead us to rethink our knowledge about Brazil and Africa.